An unexpected effect of TNF-α on F508del-CFTR maturation and function [v1; ref status: indexed, http://f1000r.es/5jf] - Sara Bitam; Iwona Pranke; Monika Hollenhorst; Nathalie Servel; Christelle Moquereau; Danielle Tondelier; Aurélie Hatton; Valérie Urbach; Isabelle Sermet-Gaudelus; Alexandre Hinzpeter; Aleksander Edelman (F1000Research, 2015)
Cystic fibrosis (CF) is a multifactorial disease caused by mutations in the cystic fibrosis transmembrane conductance regulator gene (CFTR), which encodes a cAMP-dependent Cl- channel. The most frequent mutation, F508del, leads to the synthesis of a prematurely degraded, otherwise partially functional protein. CFTR is expressed in many epithelia, with major consequences in the airways of patients with CF, characterized by both fluid transport abnormalities and persistent inflammatory responses. The relationship between the acute phase of inflammation and the expression of wild type (WT) CFTR or F508del-CFTR is poorly understood. The aim of the present study was to investigate this effect. The results show that 10 min exposure to TNF-alpha (0.5-50ng/ml) of F508del-CFTR-transfected HeLa cells and human bronchial cells expressing F508del-CFTR in primary culture (HBE) leads to the maturation of F508del-CFTR and induces CFTR chloride currents. The enhanced CFTR expression and function upon TNFα is sustained, in HBE cells, for at least 24 h. The underlying mechanism of action involves a protein kinase C (PKC) signaling pathway, and occurs through insertion of vesicles containing F508del-CFTR to the plasma membrane, with TNFα behaving as a corrector molecule. In conclusion, a novel and unexpected action of TNFα has been discovered and points to the importance of systematic studies on the roles of inflammatory mediators in the maturation of abnormally folded proteins in general and in the context of CF in particular.